2005
DOI: 10.1016/j.febslet.2005.12.040
|View full text |Cite
|
Sign up to set email alerts
|

A radical solution for the biosynthesis of the H‐cluster of hydrogenase

Abstract: Fe-only or FeFe hydrogenases, as they have more recently been termed, possess a uniquely organometallic enzyme active site, termed the H-cluster, where the electronic properties of an iron-sulfur cluster are tuned with distinctly non-biological ligands, carbon monoxide and cyanide. Recently, it was discovered that radical S-adenosylmethionine enzymes were involved in active hydrogenase expression. In the current work, we present a mechanistic scheme for hydrogenase H-cluster biosynthesis in which both carbon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 35 publications
2
61
2
Order By: Relevance
“…We can conclude that, at variance with what was proposed earlier [33], the HydG-mediated generation of initial CO and CN À precursors does not require metal-based catalysis. The latter is only required for CO synthesis.…”
Section: Discussioncontrasting
confidence: 49%
“…We can conclude that, at variance with what was proposed earlier [33], the HydG-mediated generation of initial CO and CN À precursors does not require metal-based catalysis. The latter is only required for CO synthesis.…”
Section: Discussioncontrasting
confidence: 49%
“…Sawers unpublished results). Glycine has been proposed as the direct metabolic precursor for both the cyanide and CO ligands to [FeFe]-hydrogenases [24].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the GTPase activity of this enzyme was not required for active site transfer to hydrogenase. Peters et al have also hypothesized that the diatomic CO and CN ligands are made from glycine although this activity was not assigned to any maturase in particular [29]. Our own structural studies of HydE have shown that this protein has three, evenly spaced, anion-binding sites in a large cavity, inside the (ab) 8 barrel [27].…”
Section: Introductionmentioning
confidence: 98%